2001
DOI: 10.1074/jbc.m103839200
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Conserved Residues in the GCN5 Family of Histone Acetyltransferases

Abstract: GCN5 is a critical transcriptional co-activator and is the defining member of a large superfamily of N-acetyltransferases. GCN5 catalyzes the transfer of an acetyl group from acetyl-CoA to the ⑀-amino of lysine 14 within the core H3 histone protein. Previous biochemical analyses have indicated a fully ordered kinetic mechanism. Recent structural studies have implicated several conserved residues in catalysis and substrate binding. Here the roles of Glu-173, His-145, and Asp-214 in yeast GCN5 have been evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
0
23
2
Order By: Relevance
“…In contrast to the relatively modest importance ascribed to general base function in AANAT, another member of the GNAT family, GCN-5 (as well as its close relative PCAF), has been shown to have a critical glutamate serving as a general base (26), predicted to be functionally similar to AANAT His-120 based on sequence (and three-dimensional) alignment between GCN-5 and AANAT (27). Mutation of this GCN-5 Glu residue to Gln results in an ϳ1000-fold acetyltransferase rate drop (28).…”
Section: Steady-state Kinetic Measurements For Y168fmentioning
confidence: 99%
“…In contrast to the relatively modest importance ascribed to general base function in AANAT, another member of the GNAT family, GCN-5 (as well as its close relative PCAF), has been shown to have a critical glutamate serving as a general base (26), predicted to be functionally similar to AANAT His-120 based on sequence (and three-dimensional) alignment between GCN-5 and AANAT (27). Mutation of this GCN-5 Glu residue to Gln results in an ϳ1000-fold acetyltransferase rate drop (28).…”
Section: Steady-state Kinetic Measurements For Y168fmentioning
confidence: 99%
“…Shaded text indicates conserved hydrophobic regions, and asterisks indicate positions of residues suggested to play the role of an active site base in different family members. Glu-173 has been suggested to be the active site base in tGCN5 (30,31), and His-122 has been suggested to be the active site base in AANAT (29). The alignment is based on previous structurebased alignments (16,40).…”
Section: Figmentioning
confidence: 99%
“…In members of the GNAT superfamily, there are two amino acid positions that have been suggested to act as the active site base. In the histone acetyltransferase tGCN5, Glu-173 has been suggested to fulfill this role (30,31), whereas in AANAT, the active site base appears to be His-122 (29). The three-dimensional structure of AAC(6Ј)-APH(2Љ) has not been determined, so we used available sequence alignments (16,40) to generate a partial alignment of GNAT family members that could aid in identifying the putative active site base in AAC(6Ј)-Ie (Fig.…”
Section: Mutational Analyses Of Aac(6ј)-ie Tyr-96 and Asp-99 -mentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetic and mutational studies identified residues essential for catalysis, acetyl coenzyme A binding, and histone substrate association Wang et al 1998;Tanner et al 1999;Langer et al 2001;Poux and Marmorstein 2003). The yeast Gcn5p is the catalytic subunit of several chromatographically distinct complexes including SAGA, ADA (Grant et al 1997), SALSA, and SLIK (Pray- Grant et al , 2005Sterner et al 2002a).…”
mentioning
confidence: 99%